The optimal control of power electronic embedded networks in More Electric Aircraft - Dewar, David N (2021)
With the advancement of power electronic technologies over recent decades, there has been an overall increase in the utilisation of distributed generation and power electronic embedded networks in a large sphere of applications. Probably one of the most prominent areas of utilisation of new power electronics embedded systems is the use in power networks onboard military and civilian aircraft. With environmental concerns and increased competition in the civil aviation sector, more aircraft manufactures are replacing and interfacing electrical alternatives over heavier, less efficient and costly pneumatic, hydraulic and mechanical systems. In these modern power systems, the increased proliferation of power electronic converters and distributed generation raises important issues in regards to the performance, stability and robustness between interfaced switching units. These phenomena, such as power electronic sub-system interactions, become even more prominent in micro-grid applications or other low voltage distribution systems where interfaced converters are in close proximity to one another. In More Electric Aircraft (MEA), these interfaced power electronic converters are connected to the same non-stiff low power AC grid, which further increases the interactive effects between converter sub-systems. If these effects are not properly taken into account, then external disturbances to the system at given operating conditions can result in degradation of the system performance, failure in meeting the operating requirements of the grid, or in the worst case, instability of the whole grid. With much research in the area of decreasing the size and weight of systems, there is much literature proposing optimisation methods which decrease the size of filters between interfacing converters. Whilst effectively decreasing the size of these systems, interactions between interfaced converters gets worse, and is often improperly accounted for.